Image-driven simplification with single viewpoint - Tan, Cheen-Hau (2013)
Image-driven simplification was proposed as a simplification method which generates models with high fidelity and intrinsically factors in the error from mesh appearance properties. This approach is very time consuming since it requires repeated render and image captures during simplification. Compared to the twenty viewpoints used in the original method, we propose a method which uses only a single viewpoint. The proposed single viewpoint simplification runs an estimated twenty-five times faster than the original method at comparable to better quality.